Efficacy of ferulic acid in the treatment of acute ischemic stroke injury in rats: a systematic review and meta-analysis - Wang, Jiashan; Tang, Meiqi; Xie, Xiuzhen; Xu, Yingqi; Su, Pingping; Jin, Zhuqing (Frontiers in Pharmacology, 2023)
Background: Intravenous thrombolysis is commonly used in the treatment of acute ischemic stroke damage. The existing thrombolytic drugs still suffer significant shortcomings, including a limited fibrin specificity and bleeding complications. Ferulic acid can directly bind the key thrombus enzymes and target to blood clots, suggesting its thrombolytic potency that may be beneficial with thrombolytic potency for the treatment of acute ischemic stroke damage. Objective: The purpose of this systematic review and meta-analysis was to evaluate the efficacy of ferulic acid in the treatment of acute ischemic stroke injury in rats and its potential mechanism of action. Materials and methods: We conducted a literature search in six databases, including CNKI, up to July 2023. Results: Sixteen trials were included in the meta-analysis, which demonstrated that ferulic acid significantly reduced infarct size, neurological deficit score, apoptosis index, cleaved caspase-3, and cytochrome C levels (all p < 0.05). In addition, ferulic acid significantly increased the levels of phosphorylated Akt, mitochondrial Bcl-xL/Bax, phosphorylated astrocyte PEA15, hippocampal calcium binding protein, and mitochondrial Bcl-2/Bax ratio (all p < 0.05). Conclusion: This study demonstrates that ferulic acid protects against acute ischemic stroke injury in rats by inhibiting ischemia-induced excitotoxicity, inflammatory response, and apoptosis.